The effectiveness of teaching Kazakh literature through new media resources in HIEs - Assan, N.B.; Baigutova, D.N.; Moldanova, Zh.I. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This study investigates how new media resources enhance the teaching of Kazakh literature in higher education. By integrating visualization, audio-video, and social platforms with traditional methods, the research explores their impact on student engagement and literary interest. The study analyzes the benefits and limitations of modern technologies in literary education, demonstrating the effectiveness of providing accessible electronic books, audio-video content, and social media platforms. It examines active Kazakh writers and poets on social media, literary platforms, and the web, focusing on their reader engagement strategies. The objectives and activities of literary platforms and popular social media prose and poetry pages are also analyzed. Employing theoretical, empirical (survey-based), and content analysis, the study reveals that new media fosters creativity, boosts interest in literature, and helps preserve national values in contemporary formats. While acknowledging technical and methodological challenges and proposing solutions, the research underscores the crucial role of new media in shaping the future of Kazakh literary education and its revival.